2017
DOI: 10.1021/acscombsci.6b00156
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Densely Substituted Pyrazolo[3,4-b]-4,7-dihydropyridines

Abstract: We have achieved a facile synthesis of a combinatorial library of densely substituted pyrazolo[3,4-b]-4,7-dihydropyridines- the mimics of antigenital wart drug podophyllotoxin-from 5-aminopyrazoles and 4-(methylthio) 4H-chromenes. The C(4) pyrazolyl 4H-chromenes, which also possess structural features of podophyllotoxin, were isolable intermediates in the two-step, one-pot condensation. The condensation took place in a one-pot, multicomponent manner when 3-oxo-3-phenylpropanenitriles, hydrazine (precursors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The large number of synthetic routes to pyrazolo[3,4- b ]pyridines and their applications brings great interest in this area. The most commonly applied method for the preparation of pyrazolo[3,4- b ]pyridines uses 5-aminopyrazole as synthetic precursor [ 36 39 ]. Regardless to substantial studies in this field, researchers are still focused to provide convenient regioselective synthetic methods with mild conditions and good yields of the reactions [ 40 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…The large number of synthetic routes to pyrazolo[3,4- b ]pyridines and their applications brings great interest in this area. The most commonly applied method for the preparation of pyrazolo[3,4- b ]pyridines uses 5-aminopyrazole as synthetic precursor [ 36 39 ]. Regardless to substantial studies in this field, researchers are still focused to provide convenient regioselective synthetic methods with mild conditions and good yields of the reactions [ 40 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…23 We have previously reported that the condensation of 5-amino-3-phenylpyrazoles 11 with 4H-chromenes 12 in EtOH reflux provided dihydropyazolo [3,4-b]pyridines 13 (Equation 2, Scheme 1). 24 In this remarkable transformation, initially formed C-alkylated 4H-chromene rearranged to 13 via chromene ring opening followed by recyclization. Dehydrogenation of 13 with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) provided pyrazolo [3,4-b]pyridines 14.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole is an interesting heterocycle to investigate. It has also gotten a lot of interest because it is being studied for a broad-spectrum biological property. The 1,3,4-oxadiazole is being studied because of its potentially relevant pharmacological activity. …”
Section: Introductionmentioning
confidence: 99%